2
$\begingroup$

Find the solution of given differential equation:

$$ydx-xdy+3x^2y^2e^{x^2}dx=0$$

I am not able to solve this because of $e^{x^2}$. Could someone help me with this one?

$\endgroup$
3
$\begingroup$

By dividing both side to $y^2$ we get $$ydx-xdy+3x^{ 2 }y^{ 2 }e^{ x^{ 2 } }dx=0\\ \frac { ydx-xdy }{ { y }^{ 2 } } +3x^{ 2 }e^{ x^{ 2 } }=0\\ d\left( \frac { x }{ y } \right) =3x^{ 2 }e^{ x^{ 2 } }\\ \int { d\left( \frac { x }{ y } \right) =\int { 3x^{ 2 }e^{ x^{ 2 } }dx } } =\frac { 3 }{ 2 } \int { x } d{ e }^{ { x }^{ 2 } }=\frac { 3 }{ 2 } \left( x{ e }^{ { x }^{ 2 } }-\int { { e }^{ { x }^{ 2 } }dx } \right) \\ \frac { x }{ y } =\frac { 3 }{ 2 } \left( x{ e }^{ { x }^{ 2 } }-\int { { e }^{ { x }^{ 2 } }dx } \right) +C\\ y=\frac { 2x }{ 3\left( \left( x{ e }^{ { x }^{ 2 } }-\int { { e }^{ { x }^{ 2 } }dx } \right) +C \right) } $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.